Overpopulation: effects - Bouroncle Luna, Luis (2019)
In the present work, an analysis of overpopulation is carried out, taking into account the effects in all areas of the development of society itself.he degradation of the environment is evaluated. For that, one aspect analyzed is urbanization, that is, the phenomenon of overpopulation of cities.Another point is the emission of carbon dioxide and the creation of the greenhouse effect and the consequent global warming.A second aspect that is appreciated is the shortage of food and water. It is evident that, by increasing the population, the demand for food and the consumption of water elements develop.The article ends with an emphasis on an aspect never taken into account: ethics of this aspect. An ethical reasoning about the problems of the growth of the population is exposed and it is concluded that the problem of overpopulation is a lack of education on all things.